Contact with poultry and animals increases risk of Campylobacter infections in adults of Ardabil province, Iran - Ranjbar, Reza; Babazadeh, Daryoush (Universa Medicina, 2017)
BackgroundThe acute gastroenteritis caused by campylobacteriosis is known as one of the common infectious diseases with worldwide distribution. The aim of this study was to detect Campylobacter species in stool samples by routine culturing and polymerase chain reaction (PCR) and explore the risk factors in adult subjects in East Azerbaijan province of Iran.MethodsA cross sectional study involving 1010 adult subjects, from whom stool samples were collected. Samples with inflammatory criteria like fecal leukocytes (WBC ³5) were selected and isolated through fecal lactoferrin detection test. The WBC ³5 and lactoferrin positive samples were selected for Campylobacter detection by culture and PCR methods. The required information consisting of gender, age, place of habitation, and contact with poultry and animals were asked and recorded. Chi-square test and prevalence ratio (PR) was used to analyze the data.ResultsOf 1010 stool samples, 231 (22.9 %) had WBC ³5, and from these samples 58 (25.1%) were positive by culturing and 61 (26.4 %) by PCR. Subjects having habitual contact with animals and poultry had increased risk of Campylobacter infections by 1.65 times compared with subjects without contact with animals and poultry (PR=1.65; 95% CI:1.07-2.68).ConclusionsDetection of Campylobacter infections by PCR was more sensitive in adults. Investigation of Campylobacter prevalence in Ardabil showed this bacterium should be viewed as one of the possible pathogens in inflammatory diarrheal cases. People having habitual contact with animals should check the health of the animals regularly and not consume food from suspected sources.